Membership (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1914)
NEW MEMBERS The following list comprises the names of those persons who became members during the period July 10 to Aug. 10, 1914: Members BAKER, FRED SHERMAN Tabowie, Unsan, Korea. BISSET, DANIEL GEORGE, Engr., 142 3d Ave., N. W., Edmonton So., Alberta, Canada.. BRANDT, MAURICE SHELDON, Chief Engr., White Eagle Mining & Milling Co., Box 298, Boulder, Colo. BROWNING, EDWARD, Min. Engr., Asst. to Supt., Cornwall Ore Bank Co., Cornwall, Pa. CASTLETON, WILLIAM ARTHUR, Mill Supt., East Butte Copper Mining Co., Butte, Mont. CHIDESTER, WALTER BARCLAY, Min. Engr., Care Mother Lode Mine, Greenwood, B. C., Canada. CLARK, EDWARD HARDY Mgr.,.Hearst Estate, 15 Broad St., New York, N. Y. CLARK, FREDERICK P., Chief Chem., International Lead Refining Co., East Chicago, Ind.